Rancang Bangun Sistem Informasi Wisudawan Menggunakan QR Code Berbasis Web - M. Ziaurrahman (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Administrative services to students are one thing that is important at a university. Information systems can help to simplify and speed up services. One type of administrative service is graduation management services which are still carried out manually starting from taking forms to collecting graduation. The graduation information system is one way so that graduation services can be carried out more effectively and efficiently. This research uses the waterfall method in developing software. The system is designed using data flow diagrams to describe the interaction between the user and the system. The result of this study is a website-based graduate information system that makes the graduation management process more effective, efficient, and systematic. In addition, this information system makes data reporting more controlled because the data is updated in real time.